Lewis H. Morgan on Iroquois material culture - Tooker, Elisabeth (University of Arizona Press, 1994)
In this richly illustrated volume, Elisabeth Tooker has brought together much previously unpublished material not only to show how Morgan managed such an impressive feat of scholarship but also to reveal something of his often-overlooked research methods. She provides an overview of Morgan's life and career, including his archaeological work; publishes for the first time his field notes from the three collecting trips he made for the state; reprints his description of the articles originally published in the annual reports of the Regents; and provides a classification and synopsis of the articles collected.